Rapunzel's revenge - Hale, Shannon; Hale, Dean, 1972-; Hale, Nathan, 1976- (New York : Bloomsbury, 2008)
Rapunzel is raised in a grand villa surrounded by towering walls. Rapunzel dreams of a different mother than Gothel, the woman she calls Mother. She climbs over the wall and finds out the truth. Her real mother, Kate, is a slave in Gothel's gold mine. Inthis Old West retelling, Rapunzel uses her hair as a lasso and to take on outlaws--including Gothel.
A Junior Library Guild selection
Keywords: Revenge -- Comic books, strips, etc. -- Juvenile fiction; Outlaws -- Comic books, strips, etc. -- Juvenile fiction; Cartoons and comics; Graphic novels